A call for special law enforcement awareness: The case of disaster-relief fraud (Academic Journal of Internal Affairs, 2011)
The article focuses on the complexity of challenges law enforcement agencies face during and in the aftermath of natural disasters. Using American examples, mostly incidents after the destruction of hurricane Katrina, investigating insurance- and charity fraud, fighting corruption and other white collar crimes in disaster relief and recovery are in centre of the author’s scrutiny.
Keywords: insurance fraud; disaster relief; official misconduct